Editorial for the Special Issue on Climate Change and Climate Variability, and Their Impact on Extreme Events (1st Edition) - Sridhara Nayak; Netrananda Sahu (Atmosphere)
In recent decades, the effects of climate change and climate variability have attracted significant global attention due to their growing impact on extreme weather and climate events [...]